2017
DOI: 10.3346/jkms.2017.32.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Promoter Region ofTNF-αGene in Iranian Azeri Turkish Patients with Behçet’s Disease

Abstract: Behçet’s disease (BD) is a complex chronic relapsing inflammatory disorder of unknown etiology. Alterations of the tumor necrosis factor (TNF) expression related to the polymorphic alleles of TNF gene may implicate a pathogenetic role in increased activity of this cytokine in BD. A current study aimed at investigating the possible association between BD and its clinical features in Iranian Azeri Turks with two functional TNF-α gene polymorphisms (at the positions of -238 and -857). A total number of 166 Irania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Except for IL-1 β (rs1143627) (36), these findings are in line with observations of Iranian investigations on autoimmune diseases (37, 38). Among four studied polymorphisms in TNF- α, our observation revealed that the prevalence of minor allele in rs1799724 is significantly higher in the patients than controls, confirming previously published date from Iran in inflammatory disease (39). However, this significance disappeared after correction for multiple analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Except for IL-1 β (rs1143627) (36), these findings are in line with observations of Iranian investigations on autoimmune diseases (37, 38). Among four studied polymorphisms in TNF- α, our observation revealed that the prevalence of minor allele in rs1799724 is significantly higher in the patients than controls, confirming previously published date from Iran in inflammatory disease (39). However, this significance disappeared after correction for multiple analysis.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our data, Ates and collaborators reported no association of the polymorphism and both BS clinical hallmark and severity [23]. The polymorphism did not show any association with clinical findings also in Tukish population [22,25]. Lee and colleagues studied the SNP genotypes according to the presence of uveitis, recognising that the presence of rs1800629 in patients with uveitis were not different from those without uveitis [28].…”
Section: Genotyping Ofsupporting
confidence: 89%
“…Similarly to our investigation, several studies assessed the influence of the promoter polymorphism on the expression of TNF-α in BS or its susceptibility or its severity and clinical features, as well as its role as drug-response allele [14,[22][23][24][25][26][27][28][29][30][31][32]. The effect of geographical differences, rather than the high genetic variation, are important factors for the adaptability and the evolution of any population.…”
Section: Genotyping Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, one new study was published confirming the association between Iranian BD patients and the 857T/C polymorphism [52]. Therefore, there is evidence for a genetic background for the overproduction of TNF-α in BD.…”
Section: Genetics Of Bdmentioning
confidence: 96%